Dynamical masses of M-dwarf binaries in young moving groups: I - The case of TWA 22 and GJ 2060 - Rodet, Laetitia; Homeier, Derek; Henning, Thomas (Arxiv, 2018)
Evolutionary models are widely used to infer the mass of stars, brown dwarfs, and giant planets. Their predictions are thought to be less reliable at young ages ($<$ 200 Myr) and in the low-mass regime ($\mathrm{<1~M_{\odot}}$). GJ 2060 AB and TWA 22 AB are two rare astrometric M-dwarf binaries respectively members of the AB Doradus and Beta Pictoris moving groups. As their dynamical mass can be measured within a few years, they can be used to calibrate the evolutionary tracks and set new constraints on the age of young moving groups. We find a total mass of $\mathrm{0.18± 0.02~M_\odot}$ for TWA 22. That mass is in good agreement with model predictions at the age of the Beta Pic moving group. We obtain a total mass of $\mathrm{1.09 ± 0.10~M_{\odot}}$ for GJ 2060. We estimate a spectral type of M$1±0.5$, $\mathrm{L/L_{\odot}=-1.20±0.05}$ dex, and $\mathrm{T_{eff}=3700±100}$ K for GJ 2060 A. The B component is a M$3±0.5$ dwarf with $\mathrm{L/L_{\odot}=-1.63±0.05}$ dex and $\mathrm{T_{eff}=3400±100}$ K. The dynamical mass of GJ 2060 AB is inconsistent with the most recent models predictions (BCAH15, PARSEC) for an ABDor age in the range 50-150 Myr. It is 10 to 20% (1-2 sigma, depending on the assumed age) above the models predictions, corresponding to an underestimation of $0.10$ to $0.20~\mathrm{M_\odot}$. Coevality suggests a young age for the system ($\sim$ 50 Myr) according to most evolutionary models. TWA 22 validates the predictions of recent evolutionary tracks at $\sim$20 Myr. On the other hand, we evidence a 1-2 sigma mismatch between the predicted and observed mass of GJ 2060 AB. This slight departure may indicate that one of the star hosts a tight companion. Alternatively, this would confirm the models tendency to underestimate the mass of young low-mass stars.